A study on Goethe’s ossicles in adult human skulls - PRIYA.G (International Journal of Pharma and Bio Sciences, 2019)
The interparietal part of squamous occipital bone which lies above the highest nuchal line gets ossified from two centers one on each side. The failure of fusion of ossification centers in this region leads to the development of interparietal bones or Goethe’s ossicles. These bones are rare in occurrence compared to the sutural bones in the human skull. The aim of the present study was to observe the variation in the occurrence of the interparietal bone and the findings were correlated with its ossification. The study was carried out in 25 adult dried human skulls collected from the Department of Anatomy at RVS Dental College and hospital, Coimbatore. The skulls were examined to determine the presence of interparietal bone and if so, any variations in the same. If the interparietal bone was found with variation, it was tagged and separated. Using digitalized camera, those skulls were photographed and studied. Out of 25 skulls, two skulls showed variations, one skull had a large central plate with a small lateral plate. In another skull, a central plate and a left lateral plate of interparietal bone of equal size were observed. These variations may be due to non fusion of the ossification centres in the interparietal part of the occipital bone. These nonfused plates of bones or ossicles may give a false appearance of fracture in radiological image. Therefore, anatomical knowledge of Goethe’s ossicles in the human skull is useful in the clinical practice for correct interpretation of skull radiographs to avoid diagnostic errors.